Effectiveness of topical propranolol 4% gel in the treatment of pyogenic granuloma in children. Issue 3 (28th December 2018) - Mashiah, Jacob; Hadj‐Rabia, Smail; Slodownik, Dan; Harel, Avikam; Sprecher, Eli; Kutz, Ana
Abstract: Pyogenic granuloma is a benign acquired vascular tumor that affects the skin and mucous membranes, occurring more often in children and young adults. Treatment is often required due to the associated risk of ulceration and bleeding. There are several publications reporting the use of beta‐blockers for the treatment of pyogenic granuloma. The aim of the present study was to evaluate the clinical effectiveness and safety profile of topical propranolol 4% gel for the treatment of pyogenic granuloma. A retrospective study of all cases of pyogenic granuloma treated with topical propranolol 4% gel between 2014 and 2015 was performed. Epidemiological, clinical and treatment data, including effectiveness score and safety, were reviewed. Of a total of 18 patients with pyogenic granuloma, 11 (61.1%) showed complete resolution of the lesion while two (11.1%) had an almost complete response. In three cases (16.6%), the treatment was discontinued due to bleeding, and the lesions were removed by curettage. Local irritation and lack of compliance led to treatment discontinuation in two cases. Altogether, 13 out of 18 patients (72%) had complete or almost complete response to treatment. There was a correlation between treatment duration and response to treatment. One patient only reported local side‐effects including irritation, redness and scaling of the treated area leading to discontinuation of the treatment and curettage of the pyogenic granuloma. No systemic adverse effects were reported. This is an uncontrolled retrospective study. Propranolol 4% gel may be considered as a safe and efficient topical therapy for pyogenic granuloma.